A new allele of the Brachytic2 gene in maize can efficiently modify plant architecture - Wei, Lai; Zhang, Xuan; Zhang, Zhihai; Liu, Huanhuan; Lin, Zhongwei (Heredity, 2018)
The applications of semi-dwarf genes such as sd1 and Rht1 in rice and wheat resulted in the first "green revolution" in the 1960s. However, such semi-dwarf genes that can efficiently reduce plant stature and have few negative yield traits have not yet been identified in maize. In this study, a new allele of Brachytic2 gene (qpa1) encoding P-glycoprotein was rapidly fine-mapped using a modified method. The qpa1, containing a 241-bp deletion in the last exon, had no negative effect on yield, but greatly modified the plant architecture including significantly reduced plant height and ear height, increased stalk diameter and erected leaf. A common variant similar to maize qpa1 was also present in the sorghum orthologous dw3 locus. Comparative RNA-seq analysis next showed 99 differentially co-expressed genes affected by Br2 in maize and dw3 in sorghum, including four plant height genes D3, BAK1, Actin7 and Csld1, which are involved in gibberellin and brassinosteroid biosynthesis, auxin transport and cellulose synthesis. The qpa1 can be applied to efficiently modify plant stature in maize and in combination with D3, BAK1, Actin7, Csld1 and the other 95 differentially co-expressed genes, can be edited using new genomic editing tools for further applications and studies.
Keywords: Quantitative Trait, Heritable; alely; Genes, Plant; lokus kvantitativního znaku; Genome, Plant; Alleles; sekvenční analýza RNA; genomika; kukuřice setá; rostlinné geny; genom rostlinný; Chromosomes, Plant; Inbreeding; inbreeding; fenotyp; Quantitative Trait Loci; Sequence Analysis, RNA; kvantitativní znak dědičný; Phenotype; šlechtění rostlin; Zea mays; genetické asociační studie; Genomics; mapování chromozomů; High-Throughput Nucleotide Sequencing; Chromosome Mapping; vysoce účinné nukleotidové sekvenování; chromozomy rostlin; Genetic Association Studies; Plant Breeding